The Unseen Classroom Challenge: Maping Student Experiences and Faculty Interventions on Bullying in Pakistani Higher Education - Mehvish Manzoor; Dr. Shaista Anwar (`, 2026)
This qualitative study is a research on the ongoing reality of bullying in higher education institutions in Punjab, Pakistan; disproving the false notion that bullying reduces as age advances. The study examines the prevalence, manifestations, effects, and institutional reaction to bullying through semi-structured interviews with 75 people (50 students and 25 teachers) in five universities. The results indicate that 58.7 percent of students have experienced bullying, with most of the bullying being verbal harassment (49.3 percent) and cyber-bullying. The research reveals that there has been a major shift in the bullying patterns at the university scale whereby physical aggression has been replaced by more advanced psychological and online bullying. According to both students and teachers, the consequences are severe such as psychological distress (92% of teachers, 84% of students) and academic disengagement and social isolation. In spite of these effects, the study reveals some important lapses in the systems: 8 out of 10 students have stated that they did not receive any anti-bullying programs organized on university level, and the number of teachers that have reported that they were unprepared and lacked support to take action regarding bullying cases was also 8 out of 10. The paper ends with evidence-based suggestions of extensive institutional changes, which encompass the compulsory training, open-line reporting and built-in mental health support systems, specific to the Pakistani higher learning environment. Keywords: Bullying, Higher Education, Pakistan, Student Victimization, Faculty Intervention, Cyber-bullying, Institutional Response, Qualitative Research. https://doi.org/10.5281/zenodo.18323651